2010
DOI: 10.1111/j.1750-3841.2009.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity in Barley (Hordeum Vulgare L.) Grains Roasted in a Microwave Oven under Conditions Optimized Using Response Surface Methodology

Abstract: Microwave processing and cooking of foods is a recent development that is gaining momentum in household as well as large-scale food applications. Barley contains phenol compounds which possess antioxidant activity. In this study the microwave oven roasting condition was optimized to obtain grains with high antioxidant activity measured as the ability to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical. Antioxidant activity of grains roasted under optimum conditions was assessed based on DPPH radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 42 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…Table 3 shows that TPC, and AA increased significantly by 20.1%, and 47.9% on average when AP powder was MW dried after fermentation and ultrasonication as compare to oven drying during both the processes. Some other studies have also reported that the phenolic content was increased after microwave treatment of the plant materials (Boateng, Verghese, Walker, & Ogutu, 2008;Hayat et al, 2010;Omwamba & Hu, 2010). However, Sharma and Gujral (2011) found decrease in TPC of barley after microwave cooking.…”
Section: Effect Of Drying Methods On Tpc and Aamentioning
confidence: 90%
“…Table 3 shows that TPC, and AA increased significantly by 20.1%, and 47.9% on average when AP powder was MW dried after fermentation and ultrasonication as compare to oven drying during both the processes. Some other studies have also reported that the phenolic content was increased after microwave treatment of the plant materials (Boateng, Verghese, Walker, & Ogutu, 2008;Hayat et al, 2010;Omwamba & Hu, 2010). However, Sharma and Gujral (2011) found decrease in TPC of barley after microwave cooking.…”
Section: Effect Of Drying Methods On Tpc and Aamentioning
confidence: 90%
“…Figure 1 shows and act as reductones [23] and play a major role in the reducing power of the extracts. Table 4 indicates that, when the temperature of extrusion cooking was kept constant (180°C) and feed moisture content was increased from 14% to 18%, the reducing power activity was increased significantly (p < 0.05),…”
Section: Microstructure Of Extrudatementioning
confidence: 99%
“…Similarly, in a study of alkaline‐extracted BSG phenolic extracts, the black phenolic extracts also had a higher average TPC compared with pale phenolic extracts (McCarthy et al, ). It has previously been shown that roasting barley grain increases the TPC, proportionate to roasting time, owing to the formation of Maillard browning reaction products (MRP) (Dabina‐Bicka, Karklina, & Kruma, ; Omwamba & Hu, ), also resulting in the simultaneous formation of compounds with antioxidant properties (Piggott et al, ). The TPC method is not specific to phenolic compounds as it measures any compound which is capable of reducing Folin–Ciocalteu reagent including MRP (Huang, Ou, & Prior, ).…”
Section: Resultsmentioning
confidence: 99%